2003
DOI: 10.1046/j.1526-4610.2003.03075.x
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Sumatriptan Nasal Spray in Recurrent Migrainous Headache: An Open Prospective Study

Abstract: This is the first prospective study to show that intranasal or oral sumatriptan may be effective in patients experiencing moderate to severe headache attacks which consistently do not fulfill the IHS criteria for migraine or episodic tension-type headache.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…20 The results from this small, openlabel study suggested that intranasal and oral sumatriptan may be effective for probable migraine. The current study is therefore important as it was the first large, well-controlled clinical trial to study the probable migraine population.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…20 The results from this small, openlabel study suggested that intranasal and oral sumatriptan may be effective for probable migraine. The current study is therefore important as it was the first large, well-controlled clinical trial to study the probable migraine population.…”
Section: Discussionmentioning
confidence: 87%
“…Only one other published report has evaluated the efficacy of sumatriptan in the treatment of probable migraine attacks in patients without a concomitant migraine diagnosis. 20 The results from this small, openlabel study suggested that intranasal and oral sumatriptan may be effective for probable migraine. The current study is therefore important as it was the first large, well-controlled clinical trial to study the probable migraine population.…”
Section: Discussionmentioning
confidence: 87%